2018
DOI: 10.4103/jpn.jpn_118_17
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among children who had undergone ventriculoperitoneal shunt surgery

Abstract: Background:Ventriculoperitoneal (VP) shunting is the most common neurosurgical treatment for hydrocephalus. In spite of significant developments in the technology and design of shunt systems, shunt surgery is still associated with morbidity.Aim:To identify the problems faced by children on VP shunt and assess their quality of life (QOL).Setting and Design:A cross-sectional exploratory study.Materials and Methods:A total of 31 children on VP shunt were selected through consecutive sampling technique, and hydroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Os sintomas precoces relacionados a pós operatório do implante da válvula incluem febre e convulsões, mas são associados também a patologia subjacente, mau funcionamento da derivação e infecção. Por isso, é importante conhecer quais medidas devem ser tomadas para prevenir o aparecimento de infecções (Prakash et al, 2018). Necessidade de acompanhamento ambulatorial com neurocirurgião (Tavares et al, 2020).…”
Section: Discussionunclassified
“…Os sintomas precoces relacionados a pós operatório do implante da válvula incluem febre e convulsões, mas são associados também a patologia subjacente, mau funcionamento da derivação e infecção. Por isso, é importante conhecer quais medidas devem ser tomadas para prevenir o aparecimento de infecções (Prakash et al, 2018). Necessidade de acompanhamento ambulatorial com neurocirurgião (Tavares et al, 2020).…”
Section: Discussionunclassified
“…61 Furthermore, CSF-shunt placement and subsequent revisions have been demonstrated in a recent survey of 562 patients to reduce QoL due to pain, restriction of activity due to fear of damaging the shunt, and significant number of revisions. 62,63 Mitchell et al reported an average of 10 shunt revisions per patient, 62 although the range can largely vary across surgery types. 58 This finding is consistent with existing literature.…”
Section: Effect Of Surgery Type On Hme Seizure Outcomementioning
confidence: 99%
“…The questionnaire-based on the HOQ (hydrocephalus outcome questionnaire) uses 53 items to assess the children's quality of life (15 items for the physical domain, 25 items for the social-emotional domain, 13 items for the cognitive domain) from Kulkarni 2004(Iglesias, Ros, & Martín, 2018Karmur & Kulkarni, 2017;Prakash et al, 2018). This questionnaire is used in children with age in the range of 4-18 years; and the number of males is more than female except in the research (Karmur & Kulkarni, (2017) with a difference of 1%.…”
Section: Hydrocephalus Outcome Questionnaire (Hoq)mentioning
confidence: 99%